Comparison of Vegetation Types for Prevention of Erosion and Shallow Slope Failure on Steep Slopes in the Southeastern USA - Homayra Asima; Victoria Niedzinski; Frances C. O’Donnell; Jack Montgomery (Land, 2022)
Shallow slope failures due to erosion are common occurrences along roadways. The use of deep-rooted vegetative covers is a potential solution to stabilize newly constructed slopes or repair shallow landslides. This study compared species that may provide slope stabilization for sites in the Piedmont region of the southeastern USA. Six species were tested on experimental plots under natural rainfall conditions, and vegetation health and establishment were monitored. Two methods were used to measure surface erosion, measurement of total suspended solids in collected runoff and erosion pins. While measurement uncertainty was high for both methods, differences were evident between species in the spatial distribution of surface erosion that was related to the quality of vegetation establishment. For three species that established well, soil cores were collected to measure root biomass at depths up to 40 cm. Vetiver grass (Vetiveria zizaniodies) had substantially higher mean root biomass (3.75 kg/m3) than juniper shrubs (Juniperus chinensis; 0.45 kg/m3) and fescue grass (Lolium arundinaceum; 1.28 kg/m3), with the most pronounced difference in the deepest soil layers. Seeding with turf grass such as fescue is a common practice for erosion control in the region but replacing this with vetiver on steep slopes may help prevent shallow landslides due to the additional root reinforcement. Additional work is needed to measure the magnitude of the strength gain.